Effect of Chinese herbal medicine on stroke patients with type 2 diabetes. (22nd March 2017) - Tsai, Fuu-Jen; Ho, Tsung-Jung; Cheng, Chi-Fung; Liu, Xiang; Tsang, Hsinyi; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Li, Ju-Pi; Lin, Cheng-Wen; Lin, Jaung-Geng; Lin, Jung-Chun; et al.
Abstract: Ethnopharmacological relevance: Complications of type 2 diabetes (T2D) include stroke, which is a cerebrovascular disturbance characterized by reduced blood flow in the brain, leading to death or physical disability. Chinese herbal medicine (CHM) has been widely used in ancient China for the treatment of diabetes and stroke by supplementing Qi and activating blood circulation. Aim of the study: This study aimed to investigate the frequencies and patterns of CHM treatment for stroke patients with T2D and the outcomes of long-term use in Taiwan. Materials and methods: We identified 3079 stroke patients (ICD-9-CM: 430–438) with T2D. We allocated 618 stroke patients, matched for age, gender, and T2D-to-stroke duration, to both CHM and non-CHM groups. Chi-square test, conditional multivariable logistic regression, Kaplan-Meier method, and the log-rank test were used in this study. Results: The CHM group was characterized by more cases of chronic obstructive pulmonary disease, ulcer disease, hyperlipidemia, tobacco use, and higher income. The cumulative survival probability was higher in the CHM group ( P <0.001, log rank test); after adjusting for comorbidities, income, and urbanization level, this group also exhibited a lower mortality hazard ratio (0.37, 95% confidence interval [0.25–0.55]). Shu-Jing-Huo-Xue-Tang, Xue-Fu-Zhu-Yu-Tang, and Du-Huo-Ji-Sheng-Tang; and Dan-Shen, Niu-Xi, and Yan-Hu-Suo represented the top three formulas and herbs, respectively. Conclusion: The use of CHM as adjunctive therapy may improve the overall survival (OS) of stroke patients with T2D. The list of the comprehensive herbal medicines that they used might be useful in future large-scale, randomized clinical investigations of agent effectiveness, safety, and potential interactions with conventional treatments in stroke patients with T2D. Graphical abstract: